Distortions in the International Migrant Labor Market : Evidence from Filipino Migration and Wage Responses to Destination Country Economic Shocks - McKenzie, David; Theoharides, Caroline; Yang, Dean (World Bank, Washington, DC, 2012)
The authors use an original panel dataset of migrant departures from the Philippines to identify the responsiveness of migrant numbers and wages to gross domestic product shocks in destination countries. They find a large significant elasticity of migrant numbers to gross domestic product shocks at destination, but no significant wage response. This is consistent with binding minimum wages for migrant labor. This result implies that labor market imperfections that make international migration attractive also make migrant flows more sensitive to global business cycles. Difference-in-differences analysis of a minimum wage change for maids confirms that minimum wages bind and demand is price sensitive without these distortions.